Harmonic influence of traction locomotive on hybrid DC asynchronous interconnection project. Issue 13 (4th December 2017) - Shuying, Guo; Minxiao, Han; Ruoxi, Liu; Jun, Wen
Abstract : Traction locomotive is one of the harmonic sources in power system. This study firstly analyses the principle of harmonic generation in traction locomotive, then the equivalent harmonic current source model of traction power supply system is built on the power supply bus side of traction substation. On this basis, a mathematical model is established to analyse the propagation characteristics of the harmonics generated by the traction system among different voltage levels. A harmonic transfer simulation model in PSASP was built with the actual parameters of Luxi hybrid DC asynchronous interconnection project. Using this model, the research on the influence of the traction locomotive harmonics on Luxi DC project and the AC grid connected to the project is carried out. The simulation results provide an effective guidance for reducing the adverse impact of harmonics on the hybrid DC asynchronous interconnection system and ensuring the safe operation of the project.